Cheng Te-k'un, Studies in Chinese Archaeology (Institute of Chinese Studies Centre for Chínese Archaeology and Art Studies Series No. 3), Hong Kong, The Chinese University Press, 1982, xii + 148 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1983)
-